The acceptance of TV Islamic reality shows by the Malay community - A.Manaf, Aini Maznina; Wok, Saodah; Latif, Siti Sakinah (2012)
Reality television has become increasingly popular since the past few years among viewers and television producers alike due to their own individual reasons. This study tries to understand the acceptance of the reality television, specifically, the genre of Islamic reality television shows among the Malay community. This is a quantitative study, which uses the survey method with questionnaire as the research instrument. The research targets at Malays from the age of 13 years old and above, nationwide. The study will include the level of TV viewing habits among the Malay community, the knowledge about Islamic reality show, the perception and attitude towards these programs, the reasons for watching and the satisfaction gained from watching, as well as involvement and change on the heavy viewers. Currently, a pilot study has been conducted and the full-fledged study is expected to be carried out at the end of March 2012. Communication students from different levels of programme were initially used as the starting point for the data collection. They, in turn, were asked to find other Malays, within or outside the university, from both urban and rural areas. A total 500 questionnaires are being distributed. The reliability of the questionnaire has been tested and amendments have been done for the full-fledged questionnaire. The study incorporated the uses and gratifications theory (Blumler and Katz, 1974) to understand the motives and satisfaction derived from watching Islamic reality TV. The study also tries to test the cultivation theory (Gerbner, 1986) for the heavy viewers of the Islamic reality show on their perception, attitude and behavior. The data will be analyzed using SPSS WIN 16 for descriptive statistics and inferential statistics to answer the objectives of the study and to test its hypotheses. Preliminary findings suggest that the majority of respondents have viewed an Islamic reality show; with Imam Muda as the most popular TV Islamic reality show. They believe that the program genre is good and educational in nature. The main reason for watching it is the Islamic nature and the positive learning experience gained. The respondents also stated that watching TV Islamic reality show improved their Islamic knowledge and practices. Based on the findings, it is suggested that relevant authorities take appropriate strategies to ensure that TV Islamic reality show remains relevant, fun and up-to-date with current issues for the viewers to gain new knowledge and to reinforce that their existing knowledge and practices.